1993
DOI: 10.1084/jem.177.6.1797
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of cutaneous leishmaniasis: interleukin 12 initiates a protective T helper type 1 immune response.

Abstract: Resistance to Leishmania major in mice is associated with the appearance of distinct T helper type 1 (Th1) and Th2 subsets. T cells from lymph nodes draining cutaneous lesions of resistant mice are primarily interferon gamma (IFN-gamma)-producing Th1 cells. In contrast, T cells from susceptible mice are principally Th2 cells that generate interleukin 4 (IL-4). Although existing evidence is supportive of a role for IFN-gamma in the generation of Th1 cells, additional factors may be required for a protective res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
404
6
7

Year Published

1997
1997
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 653 publications
(441 citation statements)
references
References 21 publications
24
404
6
7
Order By: Relevance
“…In infected BALB/c mice, we found that IL-12 treatment leads to Th1 cell development and lesion resolution, as previously reported (Fig. 2E) (9,10). In contrast, IL-12 administration had little effect on the course of lesion development in L. amazonensis-infected C3H mice ( Fig.…”
Section: Exogenous Il-12 Fails To Promote a Th1 Response In L Amazonsupporting
confidence: 69%
See 2 more Smart Citations
“…In infected BALB/c mice, we found that IL-12 treatment leads to Th1 cell development and lesion resolution, as previously reported (Fig. 2E) (9,10). In contrast, IL-12 administration had little effect on the course of lesion development in L. amazonensis-infected C3H mice ( Fig.…”
Section: Exogenous Il-12 Fails To Promote a Th1 Response In L Amazonsupporting
confidence: 69%
“…This finding is in striking contrast to that in L. major-infected BALB/c mice, where exogenous IL-12 treatment induces the development of a Th1 response and healing (9,10). We linked the inability of L. amazonensis-infected mice to respond to IL-12 with decreased expression of a functional IL-12R, thus providing an explanation for both why IL-12 treatment was unsuccessful and why L. amazonensis induces a nonhealing infection in mice resistant to L. major.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Previous studies have demonstrated that IL-12 plays a critical role in mediating protective immunity against L. major (14,17,18). The protective role of IL-12 in murine L. major infection has been attributed to its ability to activate NK cells and induce IFN-␥ production required to develop a Th1 cell response (19).…”
Section: Resultsmentioning
confidence: 99%
“…Related studies have shown that administration of IL-12 either just before infection or shortly after exposure to a variety of infectious organisms has proven highly effective at eliminating or decreasing infection intensity. Animals infected with Leishmania major (Sypek et al 1993, Heinzel et al 1993, Toxoplasma gondii (Gazzinelli et al 1993, Hunter et al 1995, Listeria monocytogenes (Wagner et al 1994), Cryptococcus neoformans (Clemons et al 1995), Plasmodium yoelii (Sedegah et al 1994), Mycobacterium tuberculosis (Cooper et al 1995), and Histoplasma capsulatum (Zhou et al 1995), have all benefitted from treatment with IL-12 if administered during the initial exposure to the pathogen. In our experiments however, IL-12 had little or no effect on immunity when administered alone.…”
Section: Il-12 As An Adjuvant For the Irradiated Cercariae Vaccinementioning
confidence: 99%